2023
DOI: 10.1002/anie.202313954
|View full text |Cite
|
Sign up to set email alerts
|

Reducing the Ir−O Coordination Number in Anodic Catalysts based on IrOx Nanoparticles towards Enhanced Proton‐exchange‐membrane Water Electrolysis

Hongmei Gao,
Zhaohui Xiao,
Shiqian Du
et al.

Abstract: Due to the robust oxidation conditions in strong acid oxygen evolution reaction (OER), developing an OER electrocatalyst with high efficiency remains challenging in polymer electrolyte membrane (PEM) water electrolyzer. Recent theoretical research suggested that reducing the coordination number of Ir‐O is feasible to reduce the energy barrier of the rate‐determination step, potentially accelerating the OER. Inspired by this, we experimentally verified the Ir‐O coordination number’s role at model catalysts, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…In contrast, to IrO x , catalysts with the lower CN seemed to exhibit higher performance than those rutile type. 27 In situ EXAFS spectra revealed that the Ir−O bond in low-coordinated IrO x would become shorter from 1.66 to 1.60 Å along with raising the applied bias from the OCV to 1.6 V, while nearly no change could be observed over rutile-IrO 2 (Figure 7e…”
Section: In Situ Exafsmentioning
confidence: 99%
See 3 more Smart Citations
“…In contrast, to IrO x , catalysts with the lower CN seemed to exhibit higher performance than those rutile type. 27 In situ EXAFS spectra revealed that the Ir−O bond in low-coordinated IrO x would become shorter from 1.66 to 1.60 Å along with raising the applied bias from the OCV to 1.6 V, while nearly no change could be observed over rutile-IrO 2 (Figure 7e…”
Section: In Situ Exafsmentioning
confidence: 99%
“…Based on comparing the transition of the hybridization between the O 2p and the Ru 4d t 2g /e g orbitals from the measurement of O K-edge by in situ soft XAS, the local coordination state further demonstrated that the oxygen vacancies were only formed in RuO x , confirming that OER was carried out in AEM pathway over SnRuO x while in LOM over RuO x (Figure d). In contrast, to IrO x , catalysts with the lower CN seemed to exhibit higher performance than those rutile type . In situ EXAFS spectra revealed that the Ir–O bond in low-coordinated IrO x would become shorter from 1.66 to 1.60 Å along with raising the applied bias from the OCV to 1.6 V, while nearly no change could be observed over rutile-IrO 2 (Figure e–g).…”
Section: In Situ X-ray Absorption Spectroscopy For Monitoring the Dyn...mentioning
confidence: 99%
See 2 more Smart Citations
“…To date, iridium (Ir) and its oxides are usually reported as acidic OER catalysts due to their robust activity and excellent durability. However, the extreme scarcity and high cost of Ir greatly limit its commercialization. Instead, ruthenium (Ru) with 1/8 price of Ir, present significantly higher activity than Ir catalysts, which makes it a more ideal alternative for acidic OER catalysts. , Nevertheless, the activity and stability of Ru are barely satisfactory due to its excessively strong adsorption of O-related intermediates, leaving space for the enhancement of catalytic activity and stability.…”
mentioning
confidence: 99%